Configurational paths to promoting physical activity among older adults with type 2 diabetes in China: an fsQCA study based on the multi-theory model - Zhang, Bo; Huai, Panpan; Wang, Jintao; Zhang, Linghui; Guo, Jinli (Frontiers in Endocrinology, 2025)
ObjectiveTo deeply analyzes the configurational paths to promoting physical activity in older adults with type 2 diabetes (T2DM), revealing the impact of different combinations of various factors on physical activity.MethodsThis study applied fuzzy-set qualitative comparative analysis (fsQCA) method to identify combinations of Multi-theory Model (MTM) constructs associated with higher physical activity levels.ResultsA total of 1119 older adults with T2DM were included. A single influencing factor does not constitute a necessary condition for promoting physical activity in older adults with T2DM. In contrast, two combinations of the seven influencing factors led to high level of physical activity, and substitutability and complementarity were observed among the various factors of the configuration path.ConclusionThis study confirmed that the formation of physical activity in older adults with T2DM has multiple concurrent causal relationships and multiple configuration paths. By revealing the synergy among factors, the MTM framework has been expanded. This study offers a novel configuration perspective for understanding the physical activity behavior of this population and provides key evidence for designing diverse physical activity management measures.